Using Parental Perceptions of Childhood Allergic Rhinitis to Inform Primary Care Management. (July 2014) - Garbutt, Jane M.; Sterkel, Randall; Mullen, Kathy B.; Conlon, Bridget; Leege, Erin; Bloomberg, Gordon; Strunk, Robert C.
Objective . To describe parents' experience with their child's allergic rhinitis (AR) to inform management by the primary care provider (PCP). Study Design . Two hundred parents with a child 7 to 15 years old with AR symptoms within the past 12 months completed a paper survey. Results . The child's AR was identified as a significant problem in spring (89.3%), fall (63.4%), summer (50.3%), and winter (21.4%); 51.3% had persistent disease. AR symptoms most commonly interfered with the child's outdoor activities and sleeping, and frequently bothered the parent and other family members. Most parents (88.3%) wanted to know what their child was allergic to and had many concerns about treatment options. A total of 62.9% had sought AR care from the PCP in the past 12 months. Conclusions . Many families experience significant morbidity from their child's AR and turn to their PCP for help. We identified opportunities for the PCP to reduce AR morbidity.